How to perform an accurate assessment of cardiac function in mice using high-resolution magnetic resonance imaging. - Schneider, J; Wiesmann, F; Lygate, C; Neubauer, S (2006)
High-resolution magnetic resonance cine imaging (cine-MRI) is a method that allows for a non-invasive assessment of left ventricular function and mass. To perform this quantitation, hearts are imaged from the base to the apex by a stack of two-dimensional images. Thus, analysis of myocardial mass and function by cine-MRI does not rely on geometric assumptions. Geometric and functional parameters, such as end-diastolic volume (EDV), end-systolic volume (ESV) or ejection fraction (EF), are obtained by subsequent image segmentation of the respective cine frames in each slice. While this technique has been well established in clinical practice, it is now rapidly becoming the reference method in experimental cardiovascular MRI for accurate quantification of cardiac parameters, thereby aiding the phenotyping of the increasing number of transgenic and surgical mouse models. However, accurate measurement of cardiac functional parameters requires the images to be acquired in short-axis orientation of the heart, which can be difficult to define, particularly in animals with diseased hearts. Furthermore, data analysis can be the source of a systematic error, mainly for myocardial mass measurement. Here, we describe a protocol that allows for a quick and reproducible approach of obtaining the relevant cardiac views for cine-MRI, and we explain how an accurate experimental image analysis can be performed.